Human papillomavirus in pterygium. Issue 7 (1st July 2001) - Gallagher, M J; Giannoudis, A; Herrington, C S; Hiscott, P
Abstract : AIM: To determine the prevalence and significance of human papillomaviral types in conjunctival pterygia. METHODS: Polymerase chain reaction technology was used to identify the presence of human papillomavirus (HPV) in 10 formalin fixed paraffin embedded pterygia samples. 10 conjunctival papillomas were used as positive controls. 20 conjunctival samples, 10 with primary acquired melanosis and 10 with malignant melanoma, were used as negative controls. Sample subgroups were of equal sex, race, and age distribution to eliminate bias. All samples were further analysed (for 21 HPV types) using dot-blot hybridisation techniques. RESULTS: HPV was identified in 90% of the conjunctival papillomas, 50% of the pterygia samples, but no HPV was detected in the negative control group. Two pterygia showed type 6, two type 11, and one type 16. These three HPV types were also detected in papillomas. CONCLUSION: These results suggest that HPV may be involved in the pathogenesis of pterygia and that broadly the same HPV types are found in pterygia and in papillomas. Persistent conjunctival HPV may possibly play a part in the recurrence of pterygia post excision but further larger studies are required to elucidate this hypothesis.